Energy audittng in an office building / Ahmad Khan Mohammed Noordin - Mohammed Noordin, Ahmad Khan (1999)
Energy is vital for the economie development of countries and for improving our living conditions. Energy efficiency is a process involves in using the most efficient technology, to achieve specific task, thus reducing energy consumptioa The study focuses on the existing Heat Ventilating Conditioning (HVAC) and Lighting system of the Menara Perkeso. Opportunities for improving the energy consumption were identified and evaluated. The economie analysis was carried out to determine the payback period. Good energy management should result in a reduction of usage by eliminating wastes and increasing efficiency. Energy efficiency has also several other benefits including the reduction of pollution to the environment.